ANALISA PEMILIHAN KAPAL TANPA AWAK DALAM OPERASI TINDAKAN PERLAWANAN RANJAU (TPR) DENGAN METODE AHP - Makhfud Abdullah; Fauzi Fauzi; Dimas Apriyanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The Indonesian people's understanding of the geographic constellation of Indonesia as an archipelagic country as it is today is very important, because international recognition of the form of an archipelagic state for Indonesia requires a long struggle and history. Since the 3rd United Nations Convention on the Law of The Sea Conference in 1982, it has been agreed to regulate the law of the sea regime. One of the most important decisions for Indonesia is the recognition of the form of an archipelagic state with the arrangement of rights and obligations. t present Indonesia has minesweeper ships that are members of the Fleet Mine Unit Rl. The development of technology today is experiencing rapid development in all aspects of human life. One of them is in the field of marine technology. Unmanned ships are a topic that is widely discussed because they can help ship operations in conditions that are less friendly to humans and in certain conditions, for example in mine sweeping. Planning and selecting an unmanned vessel for minesweeper in order to reduce personnel and material losses is the best choice.